Pengaruh Pinjaman Daerah Terhadap Pertumbuhan Ekonomi di Kalimantan Selatan - Asmara, Galuh Jati; Gea Dwi Asmara (Jurnal Disrupsi Bisnis, 2025)
This paper provides a template for preparing papers for electronic production of the Jurnal Ilmu Sosial dan Humaniora. A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety. The Abstract should be informative and completely self-explanatory, provide a clear statement of the problem, the proposed approach or solution, and point out major findings and and a summary of impactful conclusions. The Abstract should not be more than 250 words in length. The abstract should be written in the past tense. Standard nomenclature should be used and abbreviations should be avoided. No literature should be cited. The keyword list provides the opportunity to add keywords, used by the indexing and abstracting services, in addition to those already present in the title. Judicious use of keywords may increase the ease with which interested parties can locate our article.